DILEMA-DILEMA MANAJEMEN PUBLIK PADA SEKTOR MIGAS - Annisa Purwatiningsih (REFORMASI, 2013)
The fuel price hike by the 1 April 2012 would be a hot ball emerging into society, the polemics between the parties for and against this policy. The purpose of this paper is to analyze the critical (critically analysis) and a comprehensive review of the cases of rising fuel oil (BBM) 1 April 2012 the dilemma in terms of public management, the overall impact on system development, oil and gas and energy from the dimension of the economy and welfare of the community, influence and impact is a multiplier effect in all aspects of community life, providing a domino effect on the increase of goods, the increase in fuel compensation policy into a political commodity that is not pro-people, the dilemma that occurs when fuel prices in Indonesia are too low (the value of subsidies) so that a gap is quite far to the market price that would cause a crisis when price fluctuations and inflation is quite high. From this it would cause an even greater impact that rising unemployment and the number of poor people in Indonesia. Ways to overcome the dilemmas of the fuel price increase 1 April 2012 in terms of public management in the public do equilibrium (balance) reached between the factors that make up the dilemma.